Peran Guru Pendidikan Agama Islam Dalam Dalam Membentuk Karakter Antikorupsi di SD Al-Wasliyah Medan - Kamil, Kamil; Fuad, Ahmad; Suciani, Anggun; Ramdhani, Mutia; Hidayah, Nailla; Manurung, Nazwa Salsabia Zahra Br; Putri, Saskia Amanda; Maya, Windi Dwi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Corruption is an extraordinary crime that has a systemic impact on the character development of the younger generation. Islamic Education (PAI) teachers play a strategic role in instilling anti-corruption values based on Islamic teachings. This study aims to analyze the role of PAI teachers in shaping students' anti-corruption character through Islamic values at Al-Wasliyah Private Elementary School in Medan. This research uses a qualitative approach with a case study method. Data collection techniques were carried out through observation, in-depth interviews with PAI teachers, and documentation. The data were analyzed using a descriptive-qualitative approach. The results of the study show that PAI teachers integrate the values of honesty, responsibility, and trustworthiness into learning and religious activities at school. In conclusion, the consistent internalization of Islamic values through the role of PAI teachers proves effective in shaping students’ anti-corruption character from an early age.